Increased Endothelial Dysfunction and Insulin Resistance in Patients with Klinefelter Syndrome - Haymana, Cem; Aydogdu, Aydogan; Demirci, Ibrahim; Dinc, Mustafa; Demir, Orhan; Torun, Deniz; Yesildal, Fatih; Meric, Coskun; Basaran, Yalcin; Sonmez, Alper; Azal, Omer (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background and Objective: Patients with Klinefelter Syndrome (KS) have increased cardiometabolic risk however the pathogenesis is not clear. We investigated the presence of endothelial dysfunction, insulin resistance and inflammation in an unconfounded population of KS. Methods: A total of 32 patients with KS (mean age 21.59 ± 1.66 years) and 33 healthy control subjects (mean age: 22.15 ± 1.03 years) were enrolled. The demographic parameters, Asymmetric dimethylarginine (ADMA), homeostatic model assessment of insulin resistance (HOMA-IR) index and highsensitivity C-reactive protein (hs-CRP) levels were measured. Results: The patients had higher Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), insulin, HOMA-IR and ADMA levels (p < 0.001 for all) and lower High Density Lipoprotein Cholesterol (HDL-C) and total testosterone levels (p=0.002 and p<0.001, respectively), compared to the healthy controls. Total testosterone levels were significantly negatively correlated to ADMA (r = - 0.479, p < 0,001), hs-CRP (r = -0.291, p = 0.034) and positively correlated to HDL-C (r = 0.429, p = 0.001) levels. The multivariate analysis has shown that total testosterone (β = -0.412, p = 0.001) and TG (β = 0.332, p = 0.009) levels were the significant independent determinants of the plasma ADMA levels. Conclusion: The results of the present study show that endothelial dysfunction and insulin resistance are prevalent even in the very young subjects with KS, who have no metabolic or cardiac problems at present. Also, hypogonadism seems to play an important role for increased cardiometabolic risk in patients with KS.
Keywords: ADMA